Association of gene polymorphism of SDF1(CXCR12) with susceptibility to HIV-1 infection and AIDS disease progression: A meta-analysis - Ding, Jiwei; Zhao, Jianyuan; Zhou, Jinming; Li, Xiaoyu; Wu, Yanbin; Ge, Mei; Cen, Shan (PloS one, 2018)
Genetic polymorphism of viral receptors is relevant to risks of HIV-1 infection, while it is still under debated whether the polymorphism of SDF1, a unique ligand for HIV-1 coreceptor CXCR4, is associated with HIV susceptibility and AIDS disease progression. Therefore, we provided an updated quantitative assessment by meta-analysis from 16 case-control and 7 cohort studies. Articles reporting the relationship between SDF1 polymorphism and HIV susceptibility or AIDS progression were retrieved from PubMed, Embase and Ovid electronic databases up to Apr 2017. Data were pooled by odds ratios (ORs) for HIV-1 infection with 95% confidence intervals (CIs) and summary relative hazards (RHs) for AIDS progression with 95% CIs using 1987 Center for Disease Control (CDC) case definition of AIDS (CDC87) and 1993 Center for Disease Control (CDC) case definition of AIDS (CDC93) and death as endpoints. As a result, 16 studies regarding susceptibility to HIV-1 infection with 2803 HIV-infected patients and 3697 healthy individuals and 7 studies regarding disease progression with 4239 subjects were included in the meta-analysis. For risks of infection, no evidences indicated SDF1 polymorphism was associated with the risk of HIV-1 infection in all genetic models (recessive model: OR = 0.94, 95% Cl: 0.75-1.17; homozygous model: OR = 0.89, 95% Cl: 0.70-1.15; heterozygous model: OR = 1.06, 95% Cl: 0.83-1.35; allele model: OR = 0.95, 95% Cl: 0.79-1.13), Furthermore, we failed to find an delayed AIDS progression except in some specific cohorts including MACS cohorts (RH = 0.38, 95% Cl: 0.17-0.59 for time to AIDS; RH = 0.27, 95% Cl: 0.07-0.46 for time to death at the study entry). Overall, no significant association was found between SDF1 polymorphism and HIV susceptibility. A protective effect of SDF1 on AIDS progression and death was seen especially in two studies based on the same cohorts. In conclusion, SDF1 polymorphism exerts a moderate protective effect against AIDS disease deterioration in some specific populations.